Perforation parameters consideration for stable petroleum wellbore - Samsuri, Ariffin (1997)
The paper describes a series of laboratory experiment to observe the effects of perforation parameters and fracture zone on the wellbore stability. The wellbore stability is the most important thing that should be considered during drilling and production activities. The paper will be presented only the on effect of wellbore stability due the structure design at production zone i.e. perforated cased wellbore. Sandstone has been designed as wellbore where different perforation parameter has been imposed to see the effect on the stability i.e. shot density and perforation pattern. Then the effect of wellbore instability on sand production also analysed carefully. Generally all models fails and sand particles were produced and found that stable perforated wellbore produce less sand particles.